Загальний пайплайн розробки сучасної настольної гри - Єськова, А. С. (ХНУРЕ, 2025)
explanatory note describes the role of board games as a dynamic form of entertainment. The analysis covers various game genres, including strategic, cooperative and role-playing games, highlighting their unique mechanics and player engagement methods. Particular attention is paid to tabletop role-playing games (TTRPGs), which are built on storytelling, immersion, character development and improvisation. Popular systems like Dungeons & Dragons, FATE, and Blades in the Dark illustrate diverse approaches to gameplay and decision making. The study underscores the educational and social value of board games, demonstrating their potential for skill development, teamwork, and creative problem-solving.
Keywords: настільна гра; board games